Thiazole-induced rigidification in substituted dithieno-tetrathiafulvalene: the effect of planarisation on charge transport properties - Taylor, Rupert G. D.; Cameron, Joseph; Wright, Iain A.; Thomson, Neil; Avramchenko, Olena; Kanibolotsky, Alexander L.; Inigo, Anto R.; Tuttle, Tell; Skabara, Peter J. (Beilstein Journal of Organic Chemistry, 2015)
Two novel tetrathiafulvalene (TTF) containing compounds 1 and 2 have been synthesised via a four-fold Stille coupling between a tetrabromo-dithienoTTF 5 and stannylated thiophene 6 or thiazole 4. The optical and electrochemical properties of compounds 1 and 2 have been measured by UV–vis spectroscopy and cyclic voltammetry and the results compared with density functional theory (DFT) calculations to confirm the observed properties. Organic field effect transistor (OFET) devices fabricated from 1 and 2 demonstrated that the substitution of thiophene units for thiazoles was found to increase the observed charge transport, which is attributed to induced planarity through S–N interactions of adjacent thiazole nitrogen atoms and TTF sulfur atoms and better packing in the bulk.
Keywords: non-covalent interactions; organic field effect transistor (OFET); organic semiconductors; tetrathiafulvalene; thiazole